NEEDS ANALYSIS OF THE DEVELOPMENT OF STUDENT WORKSHEETS BASED ON HIGH ORDER THINKING SKILLS ON THE INTERACTION OF LIVING THINGS WITH THE ENVIRONMENT - Rahmita Mawadah; Zulyusri Zulyusri; Relsas Yogica; Sa'diatul Fuadiyah (Universitas Negeri Padang, 2021)
The 2013 curriculum encourages learners to have high-level high-level thinking skills high order thinking skills (HOTS). This requires teaching materials that are in line with the demands of the 2013 Curriculum such as Student Worksheets (LKPD). To develop LKPD in accordance with the demands of the 2013 Curriculum, it is necessary to analyze the needs of students about the LKPD. The purpose of this study was to see the needs of students' analysis of HOTS-based LKPD to hone higher order thinking skills so that students could think critically and creatively. This type of research is a descriptive study with a qualitative approach. The sampling technique was observation, interviews and questionnaires to students of SMPN 3 and SMPN 23 Padang. The results showed that the teaching materials available at SMPN 3 Padang and SMPN 23 Padang already used the 2013 Curriculum, but the LKPD used was only made by the Subject Teacher Conference. The LKPD made by the MGMP does not require students to analyze, evaluate and create which are indicators of HOTS. From the analysis of the curriculum, the two schools have implemented the 2013 curriculum, but in its implementate it has not emphasized a student-centered learning process. Based on the interview with the teacher, it was found that the problem in the learning process was that students were not used to higher-order thinking and there was no teaching material that specifically required students to improve higher-order thinking. Thus, the development of HOTS-based LKPD is very much needed.